CHARACTERIZATION OF DART SEQUENCES REFLECTING GENOMICREGIONS INVOLVED IN ALUMINUM TOLERANCE IN TRITICALE (X TRITICOSECALE WITTMACK) - Niedziela, Agnieszka; Bednarek, Piotr (Plant Breeding and Seed Science, 2020)
Aluminum toxicity is the major growth-limiting factor for crop cultivation on acid soils. Tolerance mecha-nisms for Al stress in triticale have not been systematically investigated so far. It is presumed, that in the case of this species they may be a function of the interaction between wheat and rye genes. In this study the se-quences of forty-six Diversity Arrays Technology markers associated with aluminum tolerance in triticale and under selection pressure were blasted against BLAST database for the identification of possible functions of the respective genome regions in Al-stress response. The analysis has showed sequences similarity to the domains involved in signaling, disease response and DNA repair mechanisms.